177k views
1 vote
Which is the value of this expression when a = negative 2 and b = negative 3? (StartFraction 3 a Superscript negative 3 Baseline b squared Over 2 a Superscript negative 1 Baseline b Superscript 0 Baseline EndFraction) squared

1 Answer

3 votes

Answer:

27/8

Explanation:

You seem to want to evaluate ...


(3a^(-3)b^2)/(2a^(-1)b^0)

I like to simplify the expression first, even though the order of operations would have you evaluate it as is.


=(3)/(2)a^(-3-(-1))b^(2-0)=(3b^2)/(2a^2)

Substitute the given values for "a" and "b" and do the arithmetic.


=(3(-3)^2)/(2(-2)^2)=(3\cdot 9)/(2\cdot 4)=\boxed{(27)/(8)}

User EdwardM
by
5.6k points